Evaluation of Brown sarson (Brassica compestris L.) genotypes for the stability of seed yield over time in temperate conditions - Mushtaq Ahmad; NR Sofi; FA Sheik; SH Wani; GH Khan (Journal of Oilseed Brassica, 2025)
This study examines the genotype-environment interaction (G × E) and seed yield stability of 10 Brassica genotypes over a five-year period (2019-2023). The results of the analysis of variance (ANOVA) revealed significant variations in genotype performance across environmental conditions, underscoring the importance of G × E interactions in influencing seed yield. Among the genotypes, KBS-63 demonstrated the highest stability and productivity, with a mean yield of 20.24 q/ha, a regression coefficient (bi) of 1.00, and a low deviation from regression (Sd² = 0.05), making it the most stable and adaptable genotype. In contrast, genotypes like SS2 and SS3, despite showing high yields under optimal conditions, exhibited low stability due to higher susceptibility to environmental stresses, with bi values of 1.10 and 0.98, respectively. The stability classification revealed that KBS-63 was highly stable, while SS2 and SS3 were classified as low-stability genotypes. These findings highlight the importance of selecting genotypes with both high yield and stability for breeding programs, particularly in regions with erratic weather patterns like the Kashmir Valley. The study emphasizes that breeding for stability, alongside yield potential, is essential for maintaining sustainable agricultural productivity in the face of climate change